2023
DOI: 10.3390/atmos14040699
|View full text |Cite
|
Sign up to set email alerts
|

Black Carbon Emissions, Transport and Effect on Radiation Forcing Modelling during the Summer 2019–2020 Wildfires in Southeast Australia

Abstract: The emission of black carbon (BC) particles, which cause atmospheric warming by affecting radiation budget in the atmosphere, is the result of an incomplete combustion process of organic materials. The recent wildfire event during the summer 2019–2020 in south-eastern Australia was unprecedented in scale. The wildfires lasted for nearly 3 months over large areas of the two most populated states of New South Wales and Victoria. This study on the emission and dispersion of BC emitted from the biomass burnings of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The normalized statistics Z(I) of the Moran's I are generally consistent with the normal distribution [67]:…”
Section: Global Spatial Autocorrelation Modelmentioning
confidence: 59%
See 1 more Smart Citation
“…The normalized statistics Z(I) of the Moran's I are generally consistent with the normal distribution [67]:…”
Section: Global Spatial Autocorrelation Modelmentioning
confidence: 59%
“…This model is extensively applied for identifying the "hot spots" or "cold spots" sin the entire area, and further classification of those spots into different spatial cluster and spatial outliners [67,68]. Local Moran's I was an indicator for spatial autocorrelation, and could be obtained by following equation:…”
Section: Local Spatial Autocorrelation Modelmentioning
confidence: 99%
“…Previous studies have shown that high concentrations of elemental carbon (i.e., black carbon produced by incomplete combustion of fossil fuels) reduces vertical mixing (Wilcox et al, 2016;Hu et al, 2020;Duc et al, 2023). This is because the black carbon emitted in the upper air mass absorbs the sunlight, which heats up faster than the air mass closest to the Earth's surface (Ding et al, 2016).…”
Section: Effect Of Local and Regional Air Mass Transport On Source Di...mentioning
confidence: 99%